EFFECT OF DIFFERENT FLOOR TYPES ON THE GROWTH PERFORMANCE AND SOME BEHAVIOURAL TRAITS OF HOLSTEIN FRIESIAN CALVES - M. Yanar; T. Z. Kartal; R. Aydin; R. Kocyigit; A. Diler (Journal of Animal and Plant Sciences, 2010)
The objective of the study was to compare growth performance, feed efficiency ratio and some behavioural characteristics of Holstein Friesian calves kept on wooden slat, rubber mats or concrete pens. The study was carried out in the Research Farm of the College of Agriculture at Atatürk University, Erzurum, Turkey by using twenty five Holstein Friesian calves (14 males and 11 females) in 2008. All pens were bedded daily with long wheat straw. While weights at weaning were not significantly affected by the type of floor, average 4 months weight of the calves housed on the slatted floor pens (93.3±2.1 kg) was significantly (P<0.05) higher than that of animals on the pens with rubber mats (83.3±2.2 kg). Total weight gains of calves on the pens with wooden slats between birth and 4 months of age (56.4±2.4 kg) was significantly (P<0.05) greater than that of the young animals on the pens with rubber mats (48.6±2.6 kg). Average amount of dry matter of the feed consumed per kg weight gains between weaning and 4 months of age was also significantly (P<0.05) lower for calves in slatted floor pens than others. Additionally, percentage of time spent for lying and standing behaviours respectively were significantly (P<0.05) higher and lower for calves in slatted floor pens than others. It is concluded that pens with wooden slats have positive effect on growth performance and behavioural characteristics of Holstein Friesian calves.
Keywords: Holstein Friesian; calves; type of floor; growth performance; behavioural traits